2023
DOI: 10.1186/s12889-023-17302-2
|View full text |Cite
|
Sign up to set email alerts
|

The burden of HEV-related acute liver failure in Bangladesh, China and India: a systematic review and meta-analysis

Rui Dong,
Dongchun Chang,
Zhenghan Luo
et al.

Abstract: Background Hepatitis E can potentially progress to HEV-related acute liver failure (HEV-ALF). East and South Asia bear a substantial burden of HEV infection, with Bangladesh, China, and India facing the most severe threat in this region. Therefore, we conducted a systematic review and meta-analysis to evaluate the burden of HEV-ALF in these three high-risk countries. Methods A systematic literature search was performed utilizing PubMed, the Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…[199][200][201][202][203] A recent metaanalysis demonstrated that among nonpregnant participants, the pooled proportion of HEV in the etiology of virus-related ALF was estimated to be 40.0%, 30.0%, and 61.0% in India, China, and Bangladesh, respectively. 204 In pregnant Indian women, the combined proportion of HEV in the etiology of viral-related ALF was 71.0%. 204 Kar et al analyzed HEV genotypes in cases of ALF and AVH in both pregnant and nonpregnant women, and found all identified isolates to be HEV-1.…”
Section: Mizuo Et Al Compared Various Features Between Patients Infectedmentioning
confidence: 99%
See 1 more Smart Citation
“…[199][200][201][202][203] A recent metaanalysis demonstrated that among nonpregnant participants, the pooled proportion of HEV in the etiology of virus-related ALF was estimated to be 40.0%, 30.0%, and 61.0% in India, China, and Bangladesh, respectively. 204 In pregnant Indian women, the combined proportion of HEV in the etiology of viral-related ALF was 71.0%. 204 Kar et al analyzed HEV genotypes in cases of ALF and AVH in both pregnant and nonpregnant women, and found all identified isolates to be HEV-1.…”
Section: Mizuo Et Al Compared Various Features Between Patients Infectedmentioning
confidence: 99%
“…204 In pregnant Indian women, the combined proportion of HEV in the etiology of viral-related ALF was 71.0%. 204 Kar et al analyzed HEV genotypes in cases of ALF and AVH in both pregnant and nonpregnant women, and found all identified isolates to be HEV-1. 195 In Western countries where HEV-3 prevails, HEV infection during pregnancy appears to pose minimal risk.…”
Section: Mizuo Et Al Compared Various Features Between Patients Infectedmentioning
confidence: 99%